Relative Mobility (Rf) Analysis of Albumin Isolates from Snakehead Fish (Ophiocephalus striatus) Extracted at Different Temperatures and Times - Matheus Nugroho; Sugiono Sugiono; Fadjar Kurnia Hartati (Food Science and Technology Journal (Foodscitech), 2021)
Snakehead fish was a fish that has a high albumin content. Snakehead fish was used in the health sector known as medicinal freshwater fish, to accelerate the process of healing wounds after surgery and childbirth. The purpose of this study was to analyze the relative mobility (Rf) of the snakehead fish (Ophiocephalus striatus) albumin isolates by steaming at different temperatures and times. The research method for analyze the relative mobility (Rf) of the snakehead fish (Ophiocephalus striatus) albumin isolates by using gel filtration column chromatography, was detected by the SDS-PAGE electrophoresis method. Electrophoresis was carried out at a constant voltage of 125 v/ slab. Gel staining was carried out with Commasie Brilliant Blue R-250 in methanol-acetic acid-water. A standard protein mixture consisting of: myosin (200.0 kDa), β-galactosidase (116.3 kDa), phosphorylase B (97.4 kDa), bovine serum albumin (66, 2 kDa), ovalbumin (45.0 kDa), carbonic anhydrose (31.0 kDa), trypsin inhibitor (21.5 kDa), lysozyme (14.4 kDa) and aprotinim (6.5 kDa). The data analysis of this research was descriptive analysis to see the photos of the electrophoresis results. Meanwhile, for the analysis, the measurement of albumin isolation by gel filtration Sephadex G-75 was carried out with a divided plot design. The results showed that SDS-PAGE electrophoresis with the most complex amount of protein was albumin isolate, the effect of the steaming temperature was 40 oC for 30 minutes, located in 5 ml of the 1st fraction, 5 ml of the 2nd fraction and 5 ml of the 3rd fraction, with values of relative mobility (Rf) 0.0833 to 0.6944.